The Celebration of the Eucharist : The Origin of the Rite and the Development of Its Interpretation - Mazza, Enrico (Book collections on Project MUSE., 1999)
Eucharistic liturgy has differed through the centuries and in different Churches. Because of these differences, it is essential that eucharistic liturgy be studied from ahistorical perspective. In The Celebration of the Eucharist, Enrico Mazza offers a thorough account of the theology of the Eucharist and presents a historical analysis of the origin and variety of eucharistic liturgies and their development in the Church. Beginning with the Last Supper, Father Mazza weaves his way through interpretations elaborated by the Fathers of the Church and medieval writers to provide the rich tapestry of concepts and categories adopted by Vatican Council II. Complete with an appendix including Jewish texts and early Eucharistic Prayers, abbreviations, bibliography, and notes, The Celebration of the Eucharist is a comprehensive source for those who have an interest in the theology of the Eucharist in the course of history.